2022
DOI: 10.1177/19400829221092638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet Exposure on the Tropical Fungi Aspergillus carbonarius and Aspergillus japonicus: Survival, Amylase Production, and Thermostability

Abstract: Background and Research Aims Although fundamental to tropical forest biodiversity, fungi have been largely neglected in conservation research. To examine the fungal response to increased ultraviolet C (UVC) radiation, we analyzed UVC radiation effects on the survival, growth, and amylase activity of Aspergillus carbonarius and Aspergillus japonicus. Methods A. carbonarius (strain URM 7305) and A. japonicus (URM 7270) were exposed to UVC (254 nm) for different periods, and morphological changes were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Transplanting was carried out periodically; the cultures were maintained at 30°C in a bacteriological oven for seven days and subsequently stored at 4°C. Fungi samples were also kept at 4 ºC on silica gel, according to previously publication [13].…”
Section: Microorganism Under Study and Maintenance Of Fungal Isolatementioning
confidence: 99%
“…Transplanting was carried out periodically; the cultures were maintained at 30°C in a bacteriological oven for seven days and subsequently stored at 4°C. Fungi samples were also kept at 4 ºC on silica gel, according to previously publication [13].…”
Section: Microorganism Under Study and Maintenance Of Fungal Isolatementioning
confidence: 99%
“…Previous studies have shown that Aspergillus japonicus is a good producer of different enzymes, such as pectinases, 9 ß‐fructofuranosidase, 10 ß‐glucosidase, 11 tannases, 12 phytases, 13 ß‐xylosidases 14 and amylases 15,16 . However, there are no reports in the literature about the biochemical characterization and the biotechnological application of the enzymes produced by this species.…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies have shown that Aspergillus japonicus is a good producer of different enzymes, such as pectinases, 9 ß-fructofuranosidase, 10 ß-glucosidase, 11 tannases, 12 phytases, 13 ß-xylosidases 14 and amylases. 15,16 However, there are no reports in the literature about the biochemical characterization and the biotechnological application of the enzymes produced by this species. Thus, this work aimed to characterize the biochemical properties of the glucoamylase from A. japonicus and assess the potential application of this enzyme in recycled paper biobleaching.…”
Section: Introductionmentioning
confidence: 99%